Region sown areas portfolio optimization taking into account crop production economic risk - P. Hrytsiuk; T. Babych; O. Mandziuk (Global Journal of Environmental Science and Management)
Grain production is one of the Ukrainian agro-industrial complex main branches. An indicator of the grain production efficiency is its profitability. It is characterized by significant annual fluctuations that induce risk. Redistribution of existing grain crops areas taking into consideration their profitability can bring to increase of production efficiency. The paper observes Markowitz’s optimal portfolio theory appliance to grain branch. The central aim of this work is the development and justification of a new technique of sown areas portfolio risk evaluating. In this study, the annual profitability of four cereal crops cultivated in the Rivne region: wheat, barley, corn, and oats, have been analyzed. It is shown that the profitability of the cereals is not normally distributed. Under these conditions, the portfolio variance loses part of its informativity and can not serve as a good risk measure. It has been determined that the profitability of crops with good precision follows Laplace distribution (double exponential distribution). The analytical expression for Value-at-Risk measures has been obtained using the Laplace distribution function. Numerical risk assessments performed. Using a modified Markowitz model and obtained risk estimates the efficient frontiers of cereal sown areas portfolios in the Rivne region were constructed. Obtained results allow indicating ways for optimization the region grain industry structure.